ANALYSIS OF BUSINESS FEASIBILITY STUDY ON BREEDING PUNGLOR KEMBANG BIRDS - Fadhlan Ridhwana Sujana; Danica Dwi Prahesti; Dewi Regamalela; MohdHaizam Saudi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This Study describe the analysis of business feasbility study of the Indonesian bird, the bird is Punglor Kembang. In our research, we explain how to business from breeding Punglor Kembang birds. The samples taken in this study are 20 respondents, they are the breeders of Punglor Kembang birds in West Java, Indonesia. This study used descriptive method with Return of Investment (ROI) and SWOT analysis.Primary and secondary data used in this research. There are four aspects that explain the business feasibility study of Punglor Kembang birds among others; marketing aspects, human resources aspects, operational & technological aspects, and financial aspect. The result of this study discovers that breedingPunglor Kembang birds in West Java is a promising business for a wide market share and this business is feasible to do because it can provide great benefits.